Correlation of Crystallin Expression and RGC Susceptibility in Experimental Glaucoma Rats of Different Ages. (3rd October 2018) - Anders, Fabian; Mann, Carolina; Liu, Aiwei; Teister, Julia; Funke, Sebastian; Thanos, Solon; Grus, Franz; Pfeiffer, Norbert; Prokosch, Verena
ABSTRACT: Purpose : Glaucoma is one of the leading causes of blindness worldwide with age being an important risk factor. However, the pathogenesis remains poorly understood. Aim of this study was to focus on age-dependent molecular changes in an experimental animal model of glaucoma. Methods : Intraocular pressure was elevated in Sprague-Dawley rats aged 3, 14, and 47 weeks for a period of 7 weeks by episcleral vein cauterization. Ganglion cell loss was monitored by an immunohistochemical staining of the Brain-specific homeobox/POU (Pit-1, Oct-2, Unc-86) domain protein 3A positive cells in retinal flat-mounts and spectral-domain optical coherence tomography measuring the retinal nerve fiber layer thickness. Molecular protein alterations were analyzed using a comprehensive mass spectrometric proteomics approach of the retina and vitreous body. Results : While juvenile animals did not show a significant loss of retinal ganglion cells due to intraocular pressure elevation, adolescent animals showed a decrease up to 26% ( p  < 0.05). A shift of retinal crystallin protein expression levels within all protein-family subclasses (α, β, γ) could be observed in the youngest animal group ( p  < 0.05), while the upregulation of crystallin proteins in older animals was less striking. In addition, numerous crystallin proteins were also detected in the vitreous body. Conclusion : These results provide insights of a potential correlation of age-related glaucomatous damage and the absence of crystallin proteins in the retina.